A redox-sensitive polymer-drug conjugate for tumor therapy: synthesis, properties and performance. (28th August 2019) - Song, Ke; Wang, Xin; Liang, Xiao; Liu, Mingxia; Zhou, Yang; Zhang, Guolin; Chen, Lijiang
Abstract: The present study aims to develop a novel intelligent polymer-drug conjugate for the delivery of gambogic acid (GA). Specifically, the conjugate was composed of polyacrylic acid, GA and cystamine. GA-loaded nanoparticles (polyacrylic acid-cystamine-gambogic acid-nanoparticles, PAA-SS-GA-NPs) were simply and rapidly prepared using an ultrasonic-assisted direct dissolution method. Subsequently, we characterized the formulation by different methods, including dynamic light scattering (DLS), differential scanning calorimetry (DSC), transmission electron microscopy (TEM) and ultraviolet spectrophotometry (UV). Moreover, the in vitro release, cytotoxicity and cellular uptake were equally determined. The results showed that PAA-SS-GA-NPs had a small particle size (91.5 ± 9.19 nm), had a high drug loading efficiency ((32.5 ± 2.3) %) and greatly improved the water solubility of GA (over 9700-fold). Most importantly, they showed good response performance. The nanoparticles maintained the antitumor activity of GA but were less cytotoxic to normal cells than free GA. These results demonstrated that the nanoparticles may be a promising drug carrier.